A case of Epstein–Barr virus-negative human immunodeficiency virus-related primary effusion lymphoma. Issue 6 (June 2018) - Ota, Shinichiro; Fujikura, Yuji; Yamamoto, Takayuki; Maki, Yohei; Kurokawa, Atsushi; Maeda, Takuya; Kanoh, Soichiro; Kawana, Akihiko
Abstract: Primary effusion lymphoma (PEL) is a rare subtype of large B-cell lymphoma associated with human herpesvirus-8. Most cases are co-infected with Epstein–Barr virus (EBV). The prognosis of PEL is extremely poor and no optimal treatment regimen has been established. We report a case of EBV-negative PEL in a 49-year-old human immunodeficiency virus-positive man, presenting with massive bilateral pleural effusion.